A novel investigation of in vitro anti-inflammatory and antioxidant activity of petroleum ether and chloroform extracts of Ficus krishnae stem bark - Amarvani P Kanjikar; Aruna LH; Ramesh L Londonkar (International Journal of Phytomedicine, 2019)
There is great importance of the genus Ficus among the living beings since time immemorial. Besides aesthetic and religious values, many species of this genus are of use in day to day life as food and in traditional medicine. Ficus krishnae belongs to the family Moraceae, which is one of the oldest plant native to India. The plant extract is used as traditional medicine for healing various diseases. The main aim of the present study was to investigate the in-vitro anti inflammation and antioxidant potential of petroleum ether and chloroform extracts of Ficus krishnae stem bark. In vitro anti-inflammatory studies were performed for the extracts of petroleum ether and chloroform using protein denaturation inhibition assay and antioxidant activity was screened by 2, 2 diphenyl-1- picrylhydrazyl (DPPH) radical scavenging assay, ABTS, Phosphomolybdenum and reducing power assay. Finally percentage of inhibition of free radical and IC50 were calculated by the help of Statistical analysis. The results of present data has shown that the Chloroform extract of Ficus krishnae stem bark has contributed in causing high potential in-vitro anti inflammation and antioxidant activity fallowed by petroleum ether extract.